Monitoring and Early Warning System for Anti-breakage of Optical Cable based on Distributed Optical Fiber Vibration Sensing - ZHANG Jun-wei; LAN Bo; HUANG Jia-geng; XIE Xiao-hua (Guangtongxin yanjiu, 2022)
In order to further strengthen the operation protection measures of the optical cable and realize real-time monitoring of the hidden danger of external force damage in the optical cable line area, this paper uses the principle of Rayleigh backscattering and coherent detection to design and construct an optical cable external damage event monitoring based on distributed optical fiber vibration sensing early warning system. Using Phase Sensitive Optical Time Domain Reflectometer (Φ-OTDR) technology, the optical fiber vibration signal is collected in real time. The key characteristics of vibration sensing are extracted, and the type of hidden danger is sent to the operation and maintenance staff to locate and warn the hidden danger of external force damage in real time. Field verification results show that the system can simultaneously detect and locate multiple vibration sources along the sensing fiber, and can identify various types of disturbance signals. The monitoring and early warning system has a complete system and a simple structure. The recognition rate of various construction signals is as high as 95%. It realizes double early warning of the type of external breakage and precise location, which can effectively prevent and stop external damage events and improve the work efficiency of anti-external breakage of optical cables.